Real-time simulation of static synchronous condenser (STATCOM) for compensation of reactive power - Abdellatif Hinda; Mounir Khiat (Institute of Advanced Engineering and Science, 2020)
This paper presents a real time simulation stability of power system by static synchronous condenser (STATCOM) in modern platform real-time simulator named (RT-LAB) using the latest INTEL quad-core processors to simulate a relatively large power system In our work, We have to study the problem of controlling voltage and reactive power in electric system by static synchronous condenser (STATCOM). All the simulations for the above work have been carried out using MATLAB /Simulink and RT-LAB Various simulations have given very satisfactory results and we have successfully improved the voltage by injecting a FACTS device, which is the STATCOM, the Studies and Comparisons of real-time simulation results of the power system with and without STATCOM connected illustrate the effectiveness and capability of STATCOM in improving voltage stability in power system.